Development Of Realistic Mathematics-Based Worksheets To Improve Students' Mathematical Problem Solving For Sequences And Series Discussions - Sitorus, Siti Shofiah (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
This study uses the Plomp model of Research and Development (R&D) with 5 stages, namely: Initial Investigation, Design, Realization/ Construction, Test, Evaluation and Revision, Implementation. The subjects of this study were 36 participants in class X TKJ 3 SMK Negeri 1 Pulau Rakyat. The instrument in this study used a questionnaire to see the validity and practicality of the media produced. The results showed that the level of validity of the learning media was 92% with a very valid category. The practicality level of the media is 84% ​​in the very practical category and the mathematics teacher questionnaire response is 95% in the very practical category. As for the level of effectiveness of the learning media based on the results of students' learning mastery after using mathematics learning media by 86% and after being developed with the Normality Gain formula it was obtained 0.355 with an index interpretation category of 0.30 < 0.70 classified as moderate which means that learning media can improve student learning outcomes. Thus, the Student Worksheet learning media is said to be feasible with valid and practical categories.